Odpowiedź :
[tex]d)\\\\3* \sqrt[3]{7}*2( \sqrt[3]{7} )^2=3*2*( \sqrt[3]{7} )^{1+2}=6( \sqrt[3]{7} )^3=6*7=42\\\\e)\\\\5 (\sqrt[3]{-3})^2*4\sqrt[3]{-6}=5*4*(\sqrt[3]{-6})^{2+1}=20(\sqrt[3]{-6})^{3}=20*(-6)=-120\\\\f)\\\\(-7\sqrt[3]{-2})^2*\sqrt[3]{-2}=(-7)^2*(\sqrt[3]{-2})^2*\sqrt[3]{-2}=49*(\sqrt[3]{-2})^{2+1}=\\\\=49*(\sqrt[3]{-2})^{3}=49*(-2)=-98[/tex]
Odpowiedź:
a)
(1/2∛12)³ = 1/8 * 12 = 1/2 * 3 = 3/2 = 1 1/2
b)
(-2∛1/4)³ = -8 * 1/4 = -2
c)
(-10∛-0,1)³ = -1000 * (-0,1) = 100
d)
3∛7 * 2(∛7)² = 6(∛7)³ = 6 * 7 = 42
e)
5(∛-6)² * 4∛-6 = 20(∛-6)³ = 20 * (-6) = -120
f)
(-7∛-2)² * ∛-2 = 49(∛-2)³ = 49 * (-2) = -98
Szczegółowe wyjaśnienie: